Monopile rotation under complex cyclic lateral loading in sand - Richards, IA; Byrne, BW; Houlsby, GT (Thomas Telford, 2019)
Monopiles supporting offshore wind turbines experience combined moment and horizontal loading which is both cyclic and complex; continuously varying in amplitude, direction and frequency. The accumulation of rotation with cyclic loading (ratcheting) is a key concern for monopile designers and has been explored in previous experimental studies, where constant amplitude cyclic tests have shown rotation to accumulate as a power law with cycle number. This paper presents results from laboratory tests in dry sand, which explore the rotation response to constant and variable amplitude, unidirectional and multidirectional cyclic loading. The tests are designed to inform model development and provide insight into key issues relevant to monopile design. Unidirectional tests show behaviour consistent with previous studies and provide a basis for interpreting more complex tests; multidirectional tests provide new insight into the monopile’s response to multidirectional cyclic loading; and multi-amplitude storm tests highlight salient features of the foundation’s response to realistic loading. Tests are conducted in both very loose and dense sand, and although the initial stiffness and capacity change, the monopile’s behaviour is qualitatively similar at both densities.